ST-ELEVATION MYOCARDIAL INFARCTION TRIGGERED BY ANAPHYLACTIC SHOCK IN AN ELDERLY PATIENT: ACASE REPORT AND LITERATURE REVIEW - Dương Trung Hào, Âu; Hoàng Phong, Ninh; Minh Khánh, Trương; Đức Khải, Lương; Duy Linh, Nguyễn; Duy Lượng, Đào; Văn Tân, Nguyễn (Journal of Health and Aging, 2025)
Acute myocardial infarction is a leading cause of mortality in the elderly; however, it may present with atypical clinical contexts that require early recognition for timely intervention. We report a unique case of a 77-year-old male with a history of chronic coronary artery disease (previous stenting) and type 2 diabetes mellitus, who developed grade III anaphylaxis following intravenous administration of cefuroxime. The patient was initially managed according to the anaphylactic shock protocol and subsequently transferred to a tertiary hospital in a hemodynamically stable condition, although persistent cutaneous allergic manifestations and dull chest pain were still present. This case illustrates a typical clinical presentation of Kounis syndrome type II (an allergic acute coronary syndrome in a patient with preexisting coronary artery disease), triggered by drug-induced anaphylaxis, and characterized by a biphasic course. In older adults, the diagnosis of Kounis syndrome is particularly challenging due to the high prevalence of underlying coronary artery disease, age-related immune alterations, and polypharmacy—factors that can themselves act as allergens. Furthermore, the elderly often exhibit atypical symptoms, complicating early recognition. Biphasic anaphylaxis, although rare, is a potentially life-threatening phenomenon, especially when superimposed on preexisting cardiovascular disease, as it may exacerbate myocardial ischemia or cause actual infarction. Vigilant monitoring during the first 24 to 72 hours following the initial anaphylactic episode is essential to enable timely detection and management of potentially life-threatening cardiovascular complications.